The Clinical Significance of Circadian Rhythm and Blood Pressure Variability - Mokhtar,R.H.; Kasim,H.H.; Ayob,A.; Maizatul Azma Masri (Universiti Sains Islam Malaysia, 2024)
Sleep-wake cycle is the most evident 24 hour rhythms observed in humans. This circadian variation is a normal biological clock. The physiological phenomenon,however has been able toexplain the onset of cardiac events that also tend to occur during certain time of day.It has been known that there is a tendency for major cardiovascular episodes to occur during the mid-morning hours. With the advent of ambulatory blood pressure monitoring, the fluctuations of blood pressure throughout the day areable to be captured. This is called blood pressure variability (BPV). The factors affecting BPV include age, sex, physical activity, mental activity, behavioural and environmental. Recent studies have shown that high BPV is associated with target organ damage, in particular cardiovascular and coronary artery diseases. In the effort to explain the mechanisms related to these complications out of excessive BPV, several studies explored the role of history of family with hypertension, hyperglycaemia and hyperlipidemia towards developing pre-existing condition that lead to high BPV.